Centralizers of Semiprime Inverse Semirings - Dog, Sonia; Florence, D. Mary; Murugesan, R.; Namasivayam, P. (Sarajevo Journal of Mathematics, 2022)
Let S be a 2-torsion free semiprime inverse semiring such that all elements of the form x+x' are in the center of S. We prove that any additive mapping FS→ S satisfying the condition 2F(xyx)+F(x)yx'+x'yF(x)=0 is a centralizer.